KINERJA KEUANGAN PERUSAHAAN PERBANKAN: INTELLECTUAL CAPITAL, SUSTAINABILITY REPORT, DAN GOOD CORPORATE GOVERNANCE - Laura, Cut; Fitri, Yulia; Ariani, Nita Erika (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
This study aims to determine the effect of intellectual capital, sustainability reports, and good corporate governance on financial performance (ROE) in banking companies listed on the Indonesia Stock Exchange (IDX). This research is quantitative. The research population is banking companies listed on the IDX for the 2017-2021 period, with a total population of 47 companies. The sampling method is purposive sampling to obtain 8 companies as research samples. The research data uses secondary data obtained from the documentation of financial reports, annual reports, and sustainability reports published on the IDX and the company website. The data analysis used was multiple linear regression using the SPSS 25 application. The results showed that intellectual capital and sustainability reports had a significant positive effect on financial performance (ROE), institutional ownership, managerial ownership, independent board of commissioners, and board of directors did not affect financial performance (ROE) in banking companies listed on the IDX for the 2017-2021 period.